The Gateway to Computer Science Excellence
0 votes
12 views

If  $2f(x)-3f(\frac{1}{x})=x^2 \: (x \neq0)$,  then $f(2)$ is

  1. $\frac{2}{3}$
  2. $ – \frac{3}{2}$
  3. $ – \frac{7}{4}$
  4. $\frac{5}{4}$
in Calculus by Boss (16.8k points)
recategorized by | 12 views

1 Answer

0 votes

Answer: $\mathbf C$

Explanation:

$2f(x) - 3f(\frac{1}{x}) = x^2\tag{1}\;\;\text{[Given]}$ 

Substitute, $x = \frac{1}{x}$, we get:

$2f(\frac{1}{x}) - 3f(x) = \frac{1}{x^2}\tag{2}$

Multiplying Equation $(1)$ by $3$, we get:

$6f(x) - 9f(\frac{1}{x}) = 3x^2\tag{3}$

Multiplying Equation $(2)$ by $2$, we get:

$4f(\frac{1}{x}) - 6f(x) = \frac{2}{x^2}\implies -6f(x) + 4f(\frac{1}{x}) = \frac{2}{x^2}\tag{4}$

Adding Equations $(3)$ and $(4)$, we get:

$f(\frac{1}{x}) = -\frac{1}{5}\left(3x^2 + \frac{2}{x^2}\right)$

Now, on putting $x = \frac{1}{2}$ in above equation, we get:

$x = -\frac{7}{4}$


$\therefore \mathbf C$ is the correct option.

by Boss (13.1k points)
edited by
Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
50,648 questions
56,459 answers
195,337 comments
100,190 users